2000
DOI: 10.1016/s1383-5866(00)00188-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface crosslinking on sieving characteristics of chitosan/poly(acrylonitrile) composite nanofiltration membranes

Abstract: Effects of surface crosslinking of chitosan/poly(acrylonitrile) (PAN) composite nanofiltration membranes at different crosslinker (glutaraldehyde) concentrations and crosslinking times on their surface chemical composition and sieving properties such as pure water permeation, molecular weight cut-off and the rejection of mono/divalent salts and mono/oligosaccharides were investigated. Fourier transform infrared-attenuated total reflectance spectroscopy (FTIR-ATRS) and X-ray photoelectron spectroscopy (XPS) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…The decrease in the peaks at 1070 and 1032 cm -1 (C-O stretching and C-N stretching in >CH-NH2 [33][34][35]) further confirms the grafting of rhFNIII7-10 at the expense of CH primary amines. Spectrum analysis also revealed an increase in the Amide I peak (C@O stretching in primary amides) amounts of rhFNIII7-10 compared with DA 4% (Fig.…”
Section: Atr-ftir Spectroscopymentioning
confidence: 86%
“…The decrease in the peaks at 1070 and 1032 cm -1 (C-O stretching and C-N stretching in >CH-NH2 [33][34][35]) further confirms the grafting of rhFNIII7-10 at the expense of CH primary amines. Spectrum analysis also revealed an increase in the Amide I peak (C@O stretching in primary amides) amounts of rhFNIII7-10 compared with DA 4% (Fig.…”
Section: Atr-ftir Spectroscopymentioning
confidence: 86%
“…The phenomenon suggested that the combination of enzymes and coatings was not based on simple blending, but on covalent incorporation of enzymes into polyurethane matrix as schematically illustrated in Scheme 1. Such covalent incorporation possibly resulted in the insertion of hydrophobic carbon skeleton, similar to some crosslinking reaction [34], therefore led to the increase in contact angle of the coating.…”
Section: Characterization Of Uwpu-l Coatingsmentioning
confidence: 98%
“…PAN is resistant to most solvents and therefore a common polymer in preparation of ultrafiltration [74], nanofiltration [75], and reverse osmosis membranes [76]. Chitosan is a hydrophilic biopolymer that is commonly used for its anti-fouling characteristics [77]. A thin layer of chitosan coated on the surface of the PAN ENM would allow water to permeate with minimum resistance and, because of its smooth surface, would minimize fouling.…”
Section: Enms As Substrate (Scaffold) In Thin Film Composite Membranesmentioning
confidence: 99%